2013
DOI: 10.1021/la403002t
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Observation of Bulk and Protein Hydration Water by Spin-Label ESR under Nanoconfinement

Abstract: Under nanoconfinement the formation of crystalline ice is suppressed, allowing the study of water dynamics at subfreezing temperatures. Here we report a temperature-dependent investigation (170-260 K) of the behavior of hydration water under nanoconfinement by ESR techniques. A 26-mer-long peptide and the Bax protein are studied. This study provides site-specific information about the different local hydrations concurrently present in the protein/peptide solution, enabling a decent comparison of the hydration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…18,22 In the very fast motional regime, 23 in which the ESR spectrum is isotropic, the hyperfine approaches A 0 , i.e., the average of the hyperfine tensor, and reflects largely local polarity. In the slow motional regime, 23 the anisotropy of the hyperfine is resolved in the spectrum, making the hyperfine splitting more sensitive to the mobility of the spin probe.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…18,22 In the very fast motional regime, 23 in which the ESR spectrum is isotropic, the hyperfine approaches A 0 , i.e., the average of the hyperfine tensor, and reflects largely local polarity. In the slow motional regime, 23 the anisotropy of the hyperfine is resolved in the spectrum, making the hyperfine splitting more sensitive to the mobility of the spin probe.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Of note, the BimBH3 used in this study is different in length from the previously reported BimBH3 (Gavathiotis et al, 2010;Walensky et al, 2006) that has weak binding affinity to BAX. Full-length BAX and variants were prepared as we previously described (Kuo et al, 2013). The typical yield (>95% purity) of 0.15 mg/l culture could reproducibly be obtained for WT BAX.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…A MTSSL nitroxide spin label, as attached to a protein, is in close vicinity (<0.7 nm in side chain length) to the protein surface; as such, its dynamical behavior is naturally correlated with the dynamics of the surrounding solvent molecules when the global tumbling motions are “frozen out” under nanoconfinement . Moreover, the improved spectroscopic sensitivity has led to the finding that the nano‐confined bulk water and the protein surface hydration are coupled to possess a similar dynamical changeover around 220 K, in line with neutron scattering results . The changeover occurs for solvent‐exposed sites in BAX, but becomes absent for buried sites, likely due to the inner hydration being too slow to be detected by cw‐ESR.…”
Section: Sensitivity Enhancement In Esr For Protein/water Interactionsmentioning
confidence: 99%
“…[84][85][86][87][88] Making use of this nanoconfinemente ffect, spin-label ESR has been improved with mesoporousm aterials such that protein and water dynamics can be studied by ESR at low temperatures withoutc ryoprotective additives. [89,90] As the global tumbling motions of ap rotein/probe are largely slowed down by nanoconfinement, ESR spectra become sensitive to dynamics related to protein backbone and internal motions even at room temperatures (Fig-ure 5A). [91][92][93][94] AM TSSL nitroxide spin label, as attachedt oa protein, is in close vicinity (< 0.7 nm in side chain length) to the protein surface; as such, its dynamical behavior is naturally correlated with the dynamics of the surrounding solventm olecules when the global tumbling motions are "frozen out" under nanoconfinement.…”
Section: Nanoconfinementimproves Cw-esr Sensitivity To Protein and Hymentioning
confidence: 99%
See 1 more Smart Citation